Assessing the Quality Gap in Medical Record Data between Underdeveloped and Non-Underdeveloped Regions based on National Health Reporting Quality Indicators - Bram Mustiko Utomo; Siswi Wulandari; Arum Sukma; Maria Yasinta Dobhe; Clara Anabel Galla (Research and Evidence on Knowledge in Administration and Management — Medical Electronic Data and Information Systems, 2025)
Accurate medical record data is crucial for effective healthcare and evidence-based policy in Indonesia. This study aimed to quantify the significant quality discrepancies—in completeness, accuracy, and timeliness—persisting between the underdeveloped 3T regions (Tertinggal, Terdepan, Terluar) and non-3T counterparts. We utilized a comparative design and analyzed multisource secondary data from the Ministry of Health, BPS, and BPJS Kesehatan (2023–2024), employing ANOVA and regression analysis on validated national reporting quality indicators. Results unequivocally demonstrate that 3T regions significantly lag non-3T areas across all metrics ($p < 0.001$). Regional classification was a powerful predictor, independently accounting for $38%$ of the variance in overall data quality (Adjusted $R^2 = 0.57$). These findings underscore the urgent need for targeted resource allocation toward digital infrastructure and capacity building in 3T regions to foster equity in health information systems, which is paramount for advancing Indonesia’s commitments to Universal Health Coverage (UHC) and the SDGs.